1995
DOI: 10.1002/nur.4770180605
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Parent Training for Promoting Positive Parent—Toddler Relationships

Abstract: The effectiveness of a parent training program for promoting positive parent-child relationships was examined among families of 2-year-olds. Forty-six mothers and fathers and their toddlers were assigned to either an intervention or comparison group. Intervention group parents participated in a 10-week program that focused on principles for effectively interacting with their toddlers. Parents completed measures of parenting self-efficacy, depression, stress, and perceptions of their toddler's behaviors and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
222
0
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(239 citation statements)
references
References 28 publications
7
222
0
10
Order By: Relevance
“…Some exceptions existed in that four studies recruited not only biological parents but also grandparents, foster parents, stepparents, and relatives (Gross et al, 2003;Gross et al, 2009;Nicholson, Anderson, Fox, & Brenner, 2002;Treacy et al, 2005). Both mothers and fathers were recruited in 19 studies (Blakemore et al, 1993;Fanning, 2007;Gross, Fogg, & Tucker, 1995;Hanisch et al, 2010;Hutchings et al, 2007;Irvine, Biglan, Smolkowski, Metzler, & Ary, 1999;Larsson et al, 2009;Matsumoto et al, 2007;Matsumoto et al, 2010;McGillicuddy, Rychtarik, Duquette, & Morsheimer, 2001;Nixon & Singer, 1993;Pisterman et al, 1992a;Pisterman et al, 1992b;Schultz et al, 1993;Taylor et al, 1998;van den Hoofdakker et al, 2007;Wang, 2005;Webster-Stratton, Kolpacoff, & Hollinsgworth, 1988;Wolfson et al, 1992). In contrast, 12 studies recruited either the mother or the father, but not both parents (Bradley et al, 2003;Cunningham, Bremmer, & Boyle, 1995;Fantuzzo et al, 2007;Gallart & Matthey, 2005;Gardner et al, 2006;Joachim et al, 2010;Martin et al, 2003;Morawska & Sanders, 2009;Patterson et al, 2002;Spaccerelli, Cotler, & Pehnman, 1992;Turner et al, 2007).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some exceptions existed in that four studies recruited not only biological parents but also grandparents, foster parents, stepparents, and relatives (Gross et al, 2003;Gross et al, 2009;Nicholson, Anderson, Fox, & Brenner, 2002;Treacy et al, 2005). Both mothers and fathers were recruited in 19 studies (Blakemore et al, 1993;Fanning, 2007;Gross, Fogg, & Tucker, 1995;Hanisch et al, 2010;Hutchings et al, 2007;Irvine, Biglan, Smolkowski, Metzler, & Ary, 1999;Larsson et al, 2009;Matsumoto et al, 2007;Matsumoto et al, 2010;McGillicuddy, Rychtarik, Duquette, & Morsheimer, 2001;Nixon & Singer, 1993;Pisterman et al, 1992a;Pisterman et al, 1992b;Schultz et al, 1993;Taylor et al, 1998;van den Hoofdakker et al, 2007;Wang, 2005;Webster-Stratton, Kolpacoff, & Hollinsgworth, 1988;Wolfson et al, 1992). In contrast, 12 studies recruited either the mother or the father, but not both parents (Bradley et al, 2003;Cunningham, Bremmer, & Boyle, 1995;Fantuzzo et al, 2007;Gallart & Matthey, 2005;Gardner et al, 2006;Joachim et al, 2010;Martin et al, 2003;Morawska & Sanders, 2009;Patterson et al, 2002;Spaccerelli, Cotler, & Pehnman, 1992;Turner et al, 2007).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Most of the studies were two-condition comparisons of group-based parenting programs against a control group (n = 37). Seven studies used a no-treatment control group (DeGarmo et al, 2004;Gammon & Rose, 1991;Greaves, 1997;Gross et al, 1995;Hanisch et al, 2010;Patterson et al, 2002;Schultz et al, 1993). Three studies used a treatment-as-usual control group (Fantuzzo et al, 2007;Hiscock et al, 2008;van den Hoofdakker et al, 2007), and three studies used an attention placebo control group (Farrar, 2005;Gutierrez 2007;Sirbu et al, 1978).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…While earlier parental training programmes, in Sweden (Socialstyrelsen, 1978(Socialstyrelsen, , 1980, as well as internationally (Bronfennbrenner, 1974;Godson and Hess, 1976;Clark-Steward and Apfel, 1978;Dembo et al, 1985;Anderson and Fox, 1990;Todres and Bunston, 1993;Mullin et al, 1994;Gross et al, 1995;Barlow, 1997;Sanders, 1999;Barlow and Stewart-Brown, 2000;Cowen, 2001;Long et al, 2001), have primarily focused on parents of young children, 'The Oxie Parents' School -Up To 19' was aimed at parents of teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown the possibility of an impact on general aspects of maternal functioning such as depression, self-efficacy and stress (Mullin et al, 1994;Gross et al, 1995;Long et al, 2001). Parental programmes may also have an effect on parents' levels of clinical anxiety and depression (Long et al, 2001), and on the quality of mother-toddler interactions (Gross et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation